OP0301 Adolescent and Young Adult Care in Adult Rheumatology: How Well Do We Know Our Heeaddss?. (15th July 2016) - Bruce, E.; Fox, J.; Samsudeen, A.; Watson, P.; Gorodkin, R.; McDonagh, J.
Abstract : Background: Most rheumatology departments will have a significantly larger cohort of older adolescents and young adults (AYAs) that enter adult services de-novo than will have transitioned from paediatric services. The current move towards a hub and spoke model of care makes it increasingly important that both secondary and tertiary care services are aware of AYA specific needs. Objectives: Our aim was to evaluate AYA care within two different adult Rheumatology clinics, in particular focusing on use of the HEEADDSS psychosocial interview. Methods: A review of clinical correspondence for 120 patients aged 16–25yrs attending adult rheumatology clinics at a secondary and tertiary care hospital in Greater Manchester, UK. Data collected focussed on evaluating the documentation of components of the HEEADDSS screen. Results: At both sites the "did not attend" rate was equal at 13%. The tertiary hospital had significantly more AYAs with Juvenile Idiopathic Arthritis (JIA) (22 patients) than the secondary care hospital (4 patients). There were differences in recording of the HEEADDSS criteria. The three most frequently documented at the tertiary hospital were drugs, education, home (41%, 36%, 19% respectively), least documented was sleep (5%). The three most often documented at the secondary care hospital were, education, exercise, activities (24%, 15%, 13% respectively), least documented was sex (1%). Conclusions: There were significantly more AYAs with JIA in the tertiary hospital. Documentation of HEEADDSS criteria varied between the two hospitals, documentation of any component was achieved in less than 50% of AYAs. A hub and spoke model of healthcare requires all adult rheumatologists to have an understanding the unique needs of AYAs. Disclosure of Interest: None declared